Laparoscopic Cecectomy for Diseases of the Appendix and Cecum - Oner, Muharrem; Abbas, Maher A. (Journal of Coloproctology, 2023)
Introduction The cecum is the first part of the large bowel. Cecectomy is a sufficient treatment for some patients, avoiding overtreatment by ileocolic resection.Purpose The goal of this study was to review a surgeon's experience with laparoscopic cecectomy and provide a technical video demonstration of this uncommon operation.Methods A retrospective chart review was conducted of all consecutive patients treated with laparoscopic cecectomy over a 16-year period. All operations were performed using a 3-trocar technique. The cecum was transected with 1 to 2 firings of a 60 millimeters linear stapler, preserving the ileocecal valve and ascending colon.Results 19 patients were identified including 12 females (63.2%). Median age was 42 years (range 16-84). Indication for surgery included appendiceal pathology in 12 patients (63.2%) and cecal abnormality in 7 (38.9%). There was no conversion to open surgery. Median intraoperative blood loss was 25 ml (range 0-150 ml) and no patient received a blood transfusion. No intraoperative or postoperative complication was noted. The median length stay was 1 day (range 0-6). Readmission rate was 0%. Final appendiceal histopathology revealed acute/chronic appendicitis in 5 patients, mucinous cystadenoma in 4 patients. Cecal histopathology revealed adenoma in 4 patients. Median follow-up was 16 months (range 4-53).Conclusions Laparoscopic cecectomy is a sufficient treatment for some patients with benign conditions of the appendix and cecum. It carries minimal morbidity. It should be considered as an alternative to segmental bowel resection in a select group of patients.
Keywords: cecum; cecectomy; appendicitis; appendiceal tumors; cecal diverticulum; cecal polyp